Implementation Of Good Manufacturing Practices (GMP) in The Home Industry of Kampung Lontong Surabaya - Yopi Riski Mei Sandra; R. Azizah; Reyna Sandrawati Cintya Dewi; Dinda Tiara Nurzahrah Dariswan (Pancasakti Journal Of Public Health Science And Research, 2025)
The implementation of Good Manufacturing Practices (GMP) is essential in preventing food contamination caused by biological, physical, or chemical hazards that may pose risks to human health. This study aims to describe the implementation of GMP in Kampung Lontong Surabaya. The research employed a descriptive observational design, which seeks to illustrate existing conditions without administering any interventions to the observed objects. Data were collected using questionnaires and observation checklists. The data were analyzed descriptively through tabulation. The implementation of GMP during the lontong production process was found to have several critical control points, as the production environment presented a relatively high risk of contamination. Overall, the food production practices in Kampung Lontong have not yet fully adopted GMP standards. It is recommended that producers place greater emphasis on personal hygiene and food sanitation, beginning with proper washing of raw ingredients and continuing through to the transportation of finished food products.